Myocardial Work Assessment for the Prediction of Prognosis in Advanced Heart Failure - Hedwig, Felix; Nemchyna, Olena; Stein, Julia; Knosalla, Christoph; Merke, Nicolas; Knebel, Fabian; Hagendorff, Andreas; Schoenrath, Felix; Falk, Volkmar; Knierim, Jan (Frontiers in Cardiovascular Medicine, 2021)
Objectives: The aim of this study was to investigate whether echocardiographic assessment of myocardial work is a predictor of outcome in advanced heart failure. Background: Global work index (GWI) and global constructive work (GCW) are calculated by means of speckle tracking, blood pressure measurement, and a normalized reference curve. Their prognostic value in advanced heart failure is unknown. Methods: Cardiopulmonary exercise testing and echocardiography with assessment of GWI and GCW was performed in patients with advanced heart failure caused by ischemic heart disease or dilated cardiomyopathy (n = 105). They were then followed up repeatedly. The combined endpoint was all-cause death, implantation of a left ventricular assist device, or heart transplantation. Results: The median patient age was 54 years (interquartile range [IQR]: 48–59.9). The mean left ventricular ejection fraction was 27.8 ± 8.2%, the median NT-proBNP was 1,210 pg/ml (IQR: 435–3,696). The mean GWI was 603 ± 329 mmHg% and the mean GCW was 742 ± 363 mmHg%. The correlation between peak oxygen uptake and GWI as well as GCW was strongest in patients with ischemic cardiomyopathy (r = 0.56, p = 0.001 and r = 0.53, p = 0.001, respectively). The median follow-up was 16 months (IQR: 12–18.5). Thirty one patients met the combined endpoint: Four patients died, eight underwent transplantation, and 19 underwent implantation of a left ventricular assist device. In the multivariate Cox regression analysis, only NYHA class, NT-proBNP and GWI (hazard ratio [HR] for every 50 mmHg%: 0.85; 95% CI: 0.77–0.94; p = 0.002) as well as GCW (HR for every 50 mmHg%: 0.86; 95% CI: 0.79–0.94; p = 0.001) were identified as independent predictors of the endpoint. The cut-off value for predicting the outcome was 455 mmHg% for GWI (AUC: 0.80; p < 0.0001; sensitivity 77.4%; specificity 71.6%) and 530 mmHg% for GCW (AUC: 0.80; p < 0.0001; sensitivity 74.2%; specificity 78.4%). Conclusions: GWI and GCW are powerful predictors of outcome in patients with advanced heart failure.